Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Paving Conblock: Studi Kasus pada CV. Regan Permata Asia - Hanik Amaria (Universitas Islam Balitar, 2022)
As many paving block factories have been established, manufacturers have to be good at determining prices and product quality in order to win the competition with other companies. The purpose of this study is to know the effect of price and product quality on purchasing decisions for paving blocks at CV. Regan Permata Asia. The research method used by the researcher is a survey technique through quantitative research approach. Researchers applied non-probability sampling with a total sample of 34 respondents. The data was obtained through the distribution of questionnaires through Google From to consumers of paving blocks on CV. Regan Permata Asia as respondent. For data management used SPSS version 18 application and Microsoft Excel. The results showed that the T test for the price variable showed a significance level of 0.001 <0.05. The product quality variable shows a significance level of 0.012 <0.005. The F-test on the price and product quality variables showed a significance level of 0.001 <0.005. So, the price variable partially has a significant effect on the decision variable to buy paving blocks at CV. Regan Permata Asia. The product quality variable partially has a significant effect on the purchasing decision variable for paving blocks, and the price variable and product quality variable simultaneously have a significant influence on the variable purchasing decisions of paving blocks at CV. Regan Permata Asia. It can be concluded the increasing value of the accuracy of pricing and product quality results in the decision to buy will be further improved